Preaching the Crusades : mendicant friars and the Cross in the thirteenth century - Maier, Christoph T. (Cambridge studies in medieval life and thought ;, 1994)
This study throws new light on both the history of the crusades and the mendicant orders in the thirteenth century. It describes the way in which the Franciscan and Dominican orders became involved in preaching the cross and examines their contribution to the crusading movement of the thirteenth century. The availability of a large number of trained preachers from the Franciscan and Dominican orders allowed the papacy to use them in order to provide the crusades with a well-organized and efficient propaganda back-up throughout Europe unknown before the thirteenth century. The book explains how the propaganda campaigns were organized and how the recruitment of crusaders took place. It shows that the mendicant friars became the most important group of crusade propagandists recruiting crusaders for virtually all thirteenth-century crusades. The book also shows that the friars were involved in providing finance for the crusades as part of their propaganda effort, despite their vows of absolute poverty. It also challenges the traditional pacifist view of the founder saints of the two orders by showing them to be supporters of the crusades themselves.